2005
DOI: 10.1016/j.actatropica.2004.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an experimental Trypanosoma congolense infection and plane of nutrition on milk production and some biochemical parameters in West African Dwarf goats

Abstract: The interactions of trypanosomosis and plane of nutrition on health and productivity of multiparous and primiparous West African Dwarf (WAD) does were studied in a multifactorial experiment including diet (supplementation or basal diet) and infection (infected or control). Experimental does were infected with Trypanosoma congolense at the beginning of the second week post-kidding and monitored for 16 weeks after infection. Trypanosome infection significantly reduced PCV (control: 30.1 ± 0.3 % vs infected: 22.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
2
5
0
2
Order By: Relevance
“…The decreased cholesterol levels observed in infected cattle in this study is consistent with findings in cattle [34], pigs [28] and sheep [35]. The high-energy demand of trypanosomes in infected animals and impaired synthesis or release of cholesterol from the liver, due to pathologic changes induced by trypanosome infection could be responsible for the decreased serum cholesterol levels [28, 36]. …”
Section: Discussionsupporting
confidence: 88%
“…The decreased cholesterol levels observed in infected cattle in this study is consistent with findings in cattle [34], pigs [28] and sheep [35]. The high-energy demand of trypanosomes in infected animals and impaired synthesis or release of cholesterol from the liver, due to pathologic changes induced by trypanosome infection could be responsible for the decreased serum cholesterol levels [28, 36]. …”
Section: Discussionsupporting
confidence: 88%
“…A significant regenerative anaemia was observed in a small number of koalas that were infected with a trypanosome as evidenced by the presence of abnormally increased numbers of reticulocytes and nucleated erythrocytes (normoblasts) supported by hypercellular bone marrow on prepared blood and bone marrow smears (A. Gillett, personal communication). Anaemia is commonly associated with human (Chisi et al 2004) and animal trypanosomiasis, reported in native African cattle breeds (Ellis et al 1987;Sekoni et al 1990;Akinbamijo et al 1998;Mahama et al 2004), horses (Silva et al 1995), pigs (Omeke and Ugwu, 1991), sheep (Katunguka-Rwakishaya et al 1992;Onah et al 1996), goats (Goossens et al 1998;Ogunsanmi and Taiwo, 2001;Faye et al 2005) and dogs (Onyeyili and Anika, 1990;Egbe-Nwiyi and Antia, 1993) and cats (Da Silva et al 2009). Anaemia is, however, not always noted with trypanosome infections, in part due to the fact that numerous trypanosomes are non-pathogenic and also due to the variable disease dynamics of pathogenic trypanosomes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that there is a correlation between the lack of nutrition and PCV levels, i.e. during dry seasons animals suffer from severe anemia which is correlated with poor nutritional conditions [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%